Gang Life in Two Cities - Robert J. DurÃ¡n (Columbia University Press, 2013)
Getting jumped into a gang was not an expected outcome for my life. I was living in Ogden, and if you asked any of the gang experts around the country they would have limited information available to comprehend gang activity in the state of Utah. This was not Boston, Chicago, Los Angeles, or New York; it was a conservative and highly religious state where everything was perceived as better than the ghetto neighborhoods that existed across the country. My homies and I were going through struggles that appeared to have no relevance to most people. We were not going to college. We were headed to the penitentiary. Some of us were headed to the cemetery. Gang members were portrayed as demons on the nightly news and in the local newspaper. Many individuals simply considered us as â€œwannabeesâ€ because the perception was that gangs existed in other places, but defi nitely not in Utah. If anything, being seen as mediocre made us represent the gang more strongly and attempt to prove by our behavior that this lifestyle was real. When individual gang members from Los Angeles or Chicago moved to Ogden, the local gangs challenged them to join a local gang or face immediate opposition. Many out-of-town gangsters chose to join local gangs, but some were able to remain separate. Several members of a well-known Los Angeles gang were able to resist and recruit local residents into their gang. The growth of this gang and its determination to establish a local presence developed into the largest gang feud in the city. Gangs in Ogden have been periodically fi ghting since the early 1980s; however, since the early 1990s reoccurring homicides and an increased number of shootings have reminded those involved with gangs that this lifestyle brought real consequences.